Eksegesis Dan Penelitian Teologis - Iwan Setiawan Tarigan (Institut Agama Kristen Negeri Tarutung, 2021)
Abstract:Theological research will achieve its true purpose when it is based on correct exegesis. Errors in exegesis will lead to errors in theological research. By definition, the term “exegesis” means to explain a word, sentence, paragraph, or entire book by leading out the true meaning (as the author intended) of a text. This is best done by going back to the original source of a text in its original language. Bible-centered Christian theological research. The Bible is the main source for God's people to know God, and the Bible needs to be studied by interpretation (exegesis). So it is clear that the Bible is the object of theological research for Christianity. This does not mean that other sources are ruled out. If God reveals Himself in general ways in areas such as nature and history (which God himself seems to teach), then researchers can also investigate nature and history to obtain additional inputs for understanding the main revelation. However, these other sources of input are not as important as the Bible. Exegesis in theological research is a must, because without exegesis, theological research as it should be will not be realized. True exegesis will produce true theology. On the other hand, wrong exegesis will produce wrong theology. Although sometimes it is difficult and there are many obstacles in carrying out exegesis, Bible students inevitably have to try to do their best in exegesis of God's Word which is the object of theological research.Keywords: exegesis, theological research Abstrak:Penelitian teologis akan mencapai tujuannya yang sesungguhnya ketika di dasari dengan eksegesis yang benar. Kesalahan dalam eksegesis akan menyebabkan kesalahan dalam penelitian teologis. Sebagai suatu definisi, istilah “eksegesis” berarti menjelaskan suatu kata, kalimat, paragraf, atau keseluruhan kitab dengan memimpin keluar pengertian sebenarnya (seperti yang dimaksudkan si penulis) dari suatu teks. Hal ini paling baik dilakukan dengan kembali kepada sumber mula-mula suatu teks dalam bahasa aslinya. Penelitian teologi Kristen yang berpusat pada Alkitab. Alkitab merupakan sumber utama umat Tuhan mengenal Allah, dan Alkitab perlu dipelajari dengan penafsiran (eksegesis). Jadi jelaslah bahwa Alkitab adalah obyek penelitian teologis bagi kekristenan. Tidak berarti bahwa sumber lainnya dikesampingkan. Apabila Allah menyatakan diri-Nya dengan cara-cara umum diberbagai bidang seperti alam dan sejarah (yang tampaknya diajarkan oleh Allah sendiri), maka peneliti juga dapat menyelidiki alam dan sejarah untuk memperoleh masukan-masukan tambahan untuk memahami penyataan yang utama tadi. Akan tetapi, sumber-sumber masukan lainnya itu tidaklah sepenting Alkitab. Eksegesis dalam penelitian teologis merupakan keharusan, karena tanpa eksegesis, maka penelitian teologis sebagaimana mestinya tidak akan terwujud. Eksegesis yang benar akan menghasilkan teologi yang benar. Sebaliknya eksegesis yang salah akan menghasilkan teologi yang salah pula. Walaupun terkadang berat dan banyak hambatan dalam melakukan eksegesis, namun pembelajar Alkitab mau tidak mau harus berusaha melakukan yang terbaik di dalam eksegesis terhadap Firman Tuhan yang merupakan obyek penelitian teologis. Kata kunci: keksegesis, penelitian teologis